2017
DOI: 10.21315/jps2017.28.s1.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Cellulases and Xylanase from Trichoderma virens UKM1 and its Potential in Oil Palm Empty Fruit Bunch (OPEFB) Saccharification

Abstract: To cite this article: Ngikoh, B. et al. (2017)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In addition, the secondary metabolites secreted by Trichoderma have a synergistic effect during the antagonistic process. Ngikoh et al [ 84 ] showed that during culturing of T. virens UKM1 with OPEFB substrate, Trichoderma degraded OPEFB by secreting cellulase and glucanase. The contents of cellulase and glucanase were the highest on the seventh day of culture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the secondary metabolites secreted by Trichoderma have a synergistic effect during the antagonistic process. Ngikoh et al [ 84 ] showed that during culturing of T. virens UKM1 with OPEFB substrate, Trichoderma degraded OPEFB by secreting cellulase and glucanase. The contents of cellulase and glucanase were the highest on the seventh day of culture.…”
Section: Discussionmentioning
confidence: 99%
“…virens made potato plants more susceptible to infection by P. infestans. T. virens is known for its production of hydrolytic enzymes such as xylanase, cellulase, endoglucanase, b-glucosidase, and exoglucanase (Amira et al, 2011;Ngikoh et al, 2017;Sood et al, 2020) that mediate several processes such as plant signaling and interaction, plant growth and resistance to pests and diseases, and cell wall dissolution of microbes (Druzhinina et al, 2011;Ahluwalia et al, 2015;Meng et al, 2019;Sood et al, 2020). In the present study, the culture filtrate of T. virens was obtained by growing the fungus on PDB medium, a rich source of cellulose, hemicellulose, lignin, and pectin of potato origin (Lesiecki et al, 2012).…”
Section: Screening For Anti-oomycete Activitymentioning
confidence: 99%
“…being among the prolific producers of xylanases, the high enzyme production cost and poor stability are major deterrents in widening their applications in the manufacturing industry. To date, xylanases producing Trichoderma species which include Trichoderma harzianum (Pathak et al 2014;Lopez-Ramirez et al 2018), T. viride (Soliman et al 2021, Ja'afaru 2013Ishida et al 2020), T. reesei (Michelin et al 2019;Hirasawa et al 2018), T. asperellum UC1 (Ezeilo et al 2019;Dortavásquez et al 2019), T. virens (Tarayre et al 2015;El-Shishtawy et al 2015;Ngikoh et al 2017), and T. pleuroticola (Korkmaz et al 2017) have been studied. Inoculation of T. virens can degrade cellulose and hemicellulose in biomass (empty fruit bunches and palm oil mill effluent) hence speed up the composting process.…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of T. virens can degrade cellulose and hemicellulose in biomass (empty fruit bunches and palm oil mill effluent) hence speed up the composting process. Trichoderma virens has been known as a potential cellulase producer particularly endoglucanase, exoglucanase and βglucosidase extracellularly for bioconversion processes and saccharification of agriculture wastes and also has good xylanase (β-xylosidase and endo-1,4-β-D-xylanase) activity (Tarayre et al 2015;Ngikoh et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation